UNVEILING THAHA HUSEIN'S CONTROVERSY ON CLASSICAL ARABIC LITERATURE EXISTENCE (CRITICAL METHODOLOGY OF THE BOOK ‘FI AL-ADAB AL-JAHILI’) - Muzakki, Akhmad (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2020)
Descartes' philosophical thinking influences the method of literary criticism developed by Thaha Husein, namely, cogito ergo sum 'I think, therefore I am.' To ensure that something exists, it must be doubted first. Likewise, the existence of jahili Arabic literature, which was conveyed verbally from generation to generation, did not rule out counterfeiting. However, Thaha Husein only saw the existence of jahili Arabic literature autonomously by denying the external factors surrounding it. Though literary works are manifestations and reflections of socio-cultural conditions that establish dialectical relations with the author, therefore, the extrinsic aspects that exist outside the text that characterize the original building of literary works cannot be ignored.